Organizational behavior : emerging realities for the workplace revolution - McShane, Steven L.; Glinow, Mary Ann Von (Boston : McGraw-Hill / Irwin, 2003)
Business
Keywords: Organizational behavior; Employee motivation; Stress management; Negotiation; Organizational leadership